Unemployment in the OECD Since the 1960s: What Do We Know? - Nickell, S; Nunziata, L; Ochel, W (2005)
This paper presents an empirical analysis of unemployment patterns in the OECD countries from the 1960s to the 1990s. Our results indicate the following. First, broad movements in unemployment across the OECD can be explained by shifts in labour market institutions. Second, interactions between average values of these institutions and shocks make no significant additional contribution to our understanding of OECD unemployment changes.